RECONSTRUCTION OF THE LEGALITY PRINCIPLE IN PENAL LAW ENFORCEMENT FOR THE REALIZATION OF JUSTICE - Iskandar Wibawa (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2018)
The legality principle is an important principle in the enforcement of penal law in addition to the culpability principle. These two principles are a requirement that must be fulfilled by the person to be penalized. However, law enforcement officers in the Criminal Justice System often only pay attention to the formulation of the legality principle in Article 1 (1) of the Criminal Code (KUHP) than the other principle that is culpability principle. So that court decisions often do not reflect a sense of justice. This is due to the interpretation of the legality principle contained in Article 1 paragraph (1) of the Criminal Code (KUHP) as “lex scripta”, “lex stricta” and “lex certa” and also the unformulated culpability principle in the Criminal Code (KUHP). Therefore, it is necessary to reconstruct the meaning of the legality principle so that it is not only understood formally, but materially by regarding the living law referred to Pancasila as a groundnorm and constitution of the UUD 1945, the legality principle is not interpreted as a certainty of law but interpreted as the principle of legal certainty. The law is not only interpreted as a written law, but also an unwritten law, so it is expected to bring about a court decision in accordance with the sense of justice.In law enforcement “in abstracto” implemented through formulation policy by penal reform in the formulation of a New Criminal Code (New KUHP), the principle of legality has been interpreted in material term that states that the source of law used by the Criminal Code is written law (Article 1) and unwritten law/ the living law (Article 2), also the culpability principle has been formulated explicitly (Article 38). Based “in abstracto” law enforcement is expected to be implemented “in inconcreto” law enforcement so as to realize court decision in accordance with the sense of community justice.